Impact of FSH on oocyte and embryo production in prepubertal gilts - Andrade, Letízzia Raposo (2024)
The aim of this study was to investigate the effects of the FSH treatment on the ovarian response of 140 days old gilts. The cumulus-oocytes complexes (COCs) were recovered from follicles of twenty-two prepubertal gilts, who were allotted to receive 100mg of FSH (treated group; n= 10) or saline solution (control group; n= 12). The percentage of small, medium and large follicles did not differ statistically (P>0.05). Concerning ovarian and uterine biometric data, the parameter “length of the left ovary” showed difference (P<0.05) (2.37 ± 0.26 for the control group and 2.49 ± 0.44 for the treated group (P= 0.02) and “thickness of the left ovary” too (1.31 ± 0.20 control group and 1.42 ± 0.41 treated group) (P=0.003). Besides that, the parameters related to the number and type of cells obtained on the last day of in vitro culture (D7) did not differ significantly (P>0.05). In terms of tendency, blastocyst conversion rate in relation to the number of morulas on day 7 (28.14 ± 13.10 – control group and 16.05 ± 14.16 – treated group) presented p-value between 0.05 and 0.10, since the control group presented higher numbers. Backfat presented tendency (P=0.09). In conclusion, due to the contradictory data regarding quantity and quality of follicles and embryos, more research is needed to fully understand the role of FSH in pre pubertal oocyte maturation in the pig, either on living gilts or being added to IVEP media.Keywords: Cumulus-Oocytes Complexes. Hormone. In Vitro Fertilization. Morula. Ovary.